Integrating pastoralism into policy process: Enhancing pastoral adaptation and sustainable development - Crane, Todd A.; Meunier, Julien (2018)
This brief is based on analysis of how past and present policy processes affect the capacity of pastoralists to adapt to climate change in Senegal, using Ngnith Municipality in the delta of the Senegal River as a case study. Drawing on a combination of literature review and original fieldwork. Our conclusions lead us to provide some recommendations which need to be more integrated in future policy-making process in order to avoid maladaptation and social inequity.